The Principle of Invariant Stress of the Surrounding Rock of the Hole under the Condition of Equal Pressure in the Deep Rock Mass - Xiangye Wu; Jingya Wang; Jingang Li; Jianwei Li; Tao Xu; Eryu Wang (Shock and Vibration)
Based on the hydrostatic pressure theory of initial stress state of rock mass, combined with Saint-Venant’s principle central idea, the principle of invariant stress of surrounding rock mass of the hole under the condition of equal pressure in deep rock mass is put forward. Numerical simulation is used to study the properties of surrounding rock and section shape of different holes, the depth of the plastic zone, the range of stress influence, and the relationship between them. The study results showed the following. (1) In the current mining depth range, it is difficult to reach the limit of 5 times the hole radius under the condition of invariant pressure of deep rock mass, and it has a significant impact on the near field and relatively small impact on the far field, reflecting the localization effect of the stress influence range. (2) The increase of stress influence range mainly moves outward with the increase of plastic zone range, and its growth slope is low and tends to be horizontal, and the increase amount is negligible. (3) When the failure range of the plastic zone of the hole is small, the influence range of the stress does not change itself, which reflects the stress invariability of the small-scale failure of the surrounding rock of the hole. The research results verify the principle of stress invariability of the surrounding rock of the hole under the condition of equal pressure of the deep rock mass, which is consistent with Saint-Venant’s central idea.